UMA PROPOSTA DE ABORDAGEM HISTÓRICO-EXPERIMENTAL DA LEI DE INDUÇÃO ELETROMAGNÉTICA DE FARADAY À LUZ DA TEORIA DA APRENDIZAGEM SIGNIFICATIVA - Labas, Marlon (2016)
The physics teaching has been done, especially in high school, by presenting concepts,equations and laws that serve to explain and to model phenomena of nature. It is very common that this approach only happens in the theoretical scope, which, in most situations,requires a great effort of abstraction by the students. Although the experimentation represents an important part and not dissociated from the teaching of science, the absence of a systematic realization of this type of activity is common in the physics teaching. Recognizing this problem, in this paper we present results of the inclusion of experimental activities and computational simulation, applied to teaching and approach of concepts related to the Faraday's law of electromagnetic induction. The theoretical basis adopted in this type of approach was the theory of meaningful learning of Ausubel and we evaluated qualitatively the student learning using the elaboration of conceptual maps before and after the approach to the subject in question, similar to what is proposed by Novak. The didactic proposal was initially offered to 51 students of two classes of third grade of high school of Escola de Educação Básica Barão de Antonina, located in Mafra - SC, in the academic year 2015. The total time for the implementation of this proposal was 10 lessons of 45 minutes each. We will see that the use of this teaching strategy and evaluation yielded beautiful works, conceptual advances and evidence of significant learning by the students. Finally, those teaching practices also served to the organization of a handbook for high school teachers, a product of this master degree, which includes: lesson plans, texts of support, experimental scripts and description of experimental kits.